Methods that are used by teachers to improve writing in the students of tenth year 9 de Octubre Highs School - Ramírez Gómez, Shirley Leonela (Machala : Universidad Técnica de Machala, 2016)
This work presents the importance of methods and strategies to develop an effective writing. methods are important in the teaching-learning process, but many teachers do not use appropriate methods and strategies to develop a meaningful learning of writing, for that reason it is very important that the teachers apply correct methods to teach english language, when teachers do not apply adequate methods there will be many deficiencies in the main skills of this language. it is notorious that writing is one of the skills that is least developed in the classroom, because some teachers do not use the correct material and many times institutions do not have the resources to develop a different class.teaching resources and motivation play an important role because they are fundamental pillars to develop an interesting class with students. if teachers managed these two aspects in a proper way could improve the english education as a second language. in addition, the strategies that english teachers use in the classroom are not adequate to teach writing. therefore, for teaching writing it is suggested to use countless activities to develop a successful english class and strategies that could be implemented to improve this skill.
Keywords: METHOD; STRATEGY; WRITING; MEANINGFUL LEARNING; ACTIVITY